Multidisciplinary amyotrophic lateral sclerosis telemedicine care: The store and forward method. Issue 1 (1st August 2018) - Pulley, Michael T.; Brittain, Rebecca; Hodges, Wayne; Frazier, Christine; Miller, Leslie; Matyjasik‐Liggett, Maria; Maurer, Susan; Peters, Melissa; Solomon, Kimberly; Berger, Alan R.
ABSTRACT: Introduction : Amyotrophic lateral sclerosis (ALS) patients benefit from multidisciplinary care in an ALS clinic. We studied whether multidisciplinary care of ALS patients using the store and forward method of telemedicine was feasible and acceptable to patients and providers. Methods : ALS patients seen in the University of Florida (UF) Jacksonville ALS clinic were eligible for our study. A trained telemedicine nurse performed and recorded a multidisciplinary assessment of the patient in their home. Clinic team members reviewed the assessments and provided recommendations, and the clinic director discussed the plan with the patient via videoconference. Patient and provider satisfaction was evaluated using surveys. Results : Eighteen patients completed a total of 27 telemedicine visits. Patient satisfaction was excellent and provider satisfaction was very good. Discussion : The store and forward method of telemedicine is an acceptable alternative to live telemedicine for the multidisciplinary care of ALS patients. This method of care may improve access to multidisciplinary care for this patient population. Muscle Nerve 59 :34–39, 2019 Abstract : See editorial on pages 3–5 in this issue .